The Regulatory Networks of the Circadian Clock Involved in Plant Adaptation and Crop Yield - Hang Xu; Xiling Wang; Jian Wei; Yi Zuo; Lei Wang (Plants, 2023)
Global climatic change increasingly threatens plant adaptation and crop yields. By synchronizing internal biological processes, including photosynthesis, metabolism, and responses to biotic and abiotic stress, with external environmental cures, such as light and temperature, the circadian clock benefits plant adaptation and crop yield. In this review, we focus on the multiple levels of interaction between the plant circadian clock and environmental factors, and we summarize recent progresses on how the circadian clock affects yield. In addition, we propose potential strategies for better utilizing the current knowledge of circadian biology in crop production in the future.